Effectiveness of digital technologies for remote monitoring of behavioral risk factors in students - A. M. Kalinina; M. S. Kulikova; V. V. Demko; A. V. Moment; R. N. Shepel; O. M. Drapkina (Кардиоваскулярная терапия и профилактика, 2025)
Aim. To evaluate the effectiveness of digital technologies for remote monitoring of modifying behavioral risk factors for excess body weight among students without chronic diseases.Material and methods. The study included 38 Pskov State University medical students without chronic diseases with a body mass index >25 kg/m2 who underwent a preventive examination. Behavioral risk factors (unhealthy diet, insufficient exercise) were modified using the Doctor PM mobile application without the involvement of medical professionals. Questionnaires (active links in the mobile app) were used to assess the attitude and opinion of users towards the remote monitoring technology. The follow-up period was 6 months.Results. Dietary habits were corrected in 77,7% of participants, including a decrease in the consumption of fats, simple carbohydrates, and salt, as well as an increase in the frequency of consumption of vegetables and fruits. Increased physical activity was noted by 71,4% of students. Body weight decreased in 65,8% of participants, of which 31,6% achieved target indicators. The majority (86,8%) rated positively the convenience and utility of personalized recommendations in the Doctor PM application.Conclusion. The first experience of practical application of digital preventive mobile technology for remote monitoring of eating habits and physical activity, as well as support for reducing excess body weight is presented using a cohort of students without chronic diseases as an example. It is important to note that the modification of behavioral risk factors occurred without medical support. Further monitoring and indepth analysis of the results are required for scaling this technology.